Pengaruh Ni Una Menos Sebagai Transnational Advocacy Networks dalam Legalisasi Aborsi di Argentina - Amirullah, Iman; Kuswardini, Seftina; Hasymi, Aditya Maulana (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2025)
Abortion has long been a controversial issue in Argentina. In the Criminal Law article 86 of 1921, the government only allows abortions to be performed in cases where the pregnancy is considered to endanger the life of the mother or when the pregnancy is a result of rape on a woman with mental disabilities. Restrictions on access to abortion result in high rates of unsafe and illegal abortions in Argentina, which increases the risk of maternal death and various other health and economic risks. The Ni Una Menos movement, which was born in 2015, became a turning point for the legalization of abortion in Argentina. Ni Una Menos successfully changed the orientation and tactics of the women's movement in Argentina, which previously focused on middle-class academia groups and political lobbying, into a movement of demonstrations and general strikes in the streets of Argentina. This movement went on to play a significant role in the enactment of rules regarding the legalization of abortion without conditions up to 14 weeks of pregnancy in 2020.